HARMONIOUS PERSONALITY DEVELOPMENT OF PRESCHOOL CHILDREN - Kadirova Dildora Najotbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the establishment of an effective preschool education system aimed at ensuring the formation of the next generation, the preparation of educational-methodical, didactic materials, and artistic literature reflecting national, cultural, and historical values, and the arousal of interest in reading books from childhood, as well as the implementation of the project under a public-private partnership agreement.